The Urgency of Halal Transportation and Logistics to Ensure the Safety of Consumer - Frida Karima; Khafidz Ma'shum; Uswatun Khasanah; Hendri Hermawan Adinugraha (Universitas Darussalam Gontor, 2024)
Consumer protection in halal transportation is increasingly crucial amid industry growth and heightened public awareness. As an integral part of the halal supply chain, ensuring product safety during transportation is paramount, going beyond halal compliance. Specific practices, from packaging to logistical governance, are vital at each stage. This study underscores the urgency of implementing halal transportation practices for consumer protection and explores their positive impacts on goods' safety and integrity. The literature review offers insights from various studies, emphasizing legal efforts, government and society roles, and transportation service providers responsibilities. The study concludes that halal transportation practices, beyond certification, encompass safety, security, comfort, and sustainability, supporting consumer trust, meeting demands, enhancing industry competitiveness, and contributing to environmental sustainability. Overall, implementing halal transportation practices is a strategic step for comprehensive consumer protection and industry success.